Boosting construction workers’ performances through motivation: a study in Ghana / Zakari Mustapha ... [et al.] - Mustapha, Zakari; Akoma, Benjamin Boahene; Mensah, David; Wisdom, Gbettey; Tieru, Chris Kurbom (UiTM Press, 2024)
Motivation is essential for boosting worker’s performance to achieve high productivity within an organisation. This study investigates the impact of various motivational strategies on construction worker performance in Cape Coast Metropolis, Ghana. We aim to identify the key factors that enhance employee engagement and productivity, informing effective management practices within the construction industry. A quantitative survey was conducted among construction professionals, including architects, quantity surveyors, civil engineers, builders, and artisans. Participants were selected from various company sizes (small, medium, and large) and experience levels (five to thirtyfive years) to capture diverse perspectives and ensure some level of representativeness within the targeted population. Descriptive statistics and Relative Importance Index (RII) were employed to analyse data on employee perceptions of motivation and its impact on performance. Open-ended responses provided additional insights and context. The study reveals a strong link between motivation and construction worker performance. Factors like fair compensation, clear career development prospects, and a positive work environment were key motivators. Monetary rewards alone were deemed less impactful, highlighting the importance of both intrinsic and extrinsic motivators. The study is limited to the generalisable construction industry in Ghana; regional variations and cultural factors may require further investigation. The self-reported nature of the data poses potential bias, and future research could explore targeted interventions and leadership styles to refine motivational strategies. This study contributes to understanding motivation within the construction industry, offering valuable insights for practitioners to optimise workforce performance and boost productivity.